8 - L’État et la santé sexuelle des personnes en situation de handicap au Cameroun - Magne, Estelle Kouokam; Chiewouo, Irene Flore; Djoukouo, Felicite (Africa Development, 2024)
From a socio-historical and anthropological perspective, this article aims to answer the following questions: Why is the sexual health of people with disabilities “forgotten” in institutional arrangements? What does this oversight tell of the values conferred to the person in our contemporary social and political context? How is taking into account the sexual health of people with disabilities a citizenship issue? By adopting a structuralist and intersectional perspective, the article seeks to understand and analyze the social and historical dynamics that explain this institutional omission of people with disabilities in the development of public policies relating to sexual health in Cameroon.